2016
DOI: 10.18632/oncotarget.13248
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of pretreatment elevated platelet count in patients with colorectal cancer: a meta-analysis

Abstract: BackgroundThe prognostic effect of pretreatment elevated platelet count remains controversial in colorectal cancer patients. We conducted this meta-analysis to evaluate the prognostic impact of it in these patients.MethodsPubMed, EMBASE and Cochrane Library were searched and studies on the prognostic significance of pretreatment elevated platelet count in colorectal patients were identified. We performed the meta-analysis, using overall survival and disease-free survival as outcomes and presenting data with ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 52 publications
0
29
1
Order By: Relevance
“…62 These interactions between tumor cells and platelets contribute to poor prognosis in patients with cancer. 19,20,[23][24][25][26][27][28]30,32,33,63 Studies regarding HNSCC, most of which have been published over the past few years (Tables 1 34-40,51 and 2 37,38,[41][42][43][44][45][46]51 ), showed differing disease sites, stage of disease, treatment modalities, cutoff values, and primary end points. 15,16 An increasing number of studies are investigating the association between thrombocytosis and mortality in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…62 These interactions between tumor cells and platelets contribute to poor prognosis in patients with cancer. 19,20,[23][24][25][26][27][28]30,32,33,63 Studies regarding HNSCC, most of which have been published over the past few years (Tables 1 34-40,51 and 2 37,38,[41][42][43][44][45][46]51 ), showed differing disease sites, stage of disease, treatment modalities, cutoff values, and primary end points. 15,16 An increasing number of studies are investigating the association between thrombocytosis and mortality in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 An increasing number of studies are investigating the association between thrombocytosis and mortality in patients with cancer. 19,20,[23][24][25][26][27][28]30,32,33,63 Studies regarding HNSCC, most of which have been published over the past few years (Tables 1 [34][35][36][37][38][39][40]51 and 2 37,38,[41][42][43][44][45][46]51 ), showed differing disease sites, stage of disease, treatment modalities, cutoff values, and primary end points. Thus, the reported impact of elevated platelet count and PLR differs significantly among studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated platelets also release pro-inflammatory mediators which interfere in the pathophysiology of MetS 42. The latest meta-analysis reported that elevated platelet count and thrombocytosis prior to treatment, was related with a poor prognosis for patients with CRC 43,44. Lymphocytes play a vital role in cancer immune surveillance and suppress tumor maturation 45.…”
Section: Discussionmentioning
confidence: 99%